Nutritional status, healthy eating index and eating attitudes of the adolescents in Istanbul: A cross-sectional study - AKMAN, MEHMET (Walter de Gruyter GmbH, 2015)
Background: The aim of this study was to evaluate dietary quality of adolescents by using the Healthy Eating Index (HEI) and to assess their eating attitudes by the EAT-26 Eating Attitude Test. Methods: Eight schools; four primary schools and four secondary schools were randomly selected from the school list of official website of Istanbul Education National Directorate. Five hundred and ninety-eight students who met the inclusion criteria included in the study, 24 h dietary recalls were collected to calculate their HEI scores and eating attitudes were evaluated by EAT-26 Eating Attitude Test. Their weight, height and waist circumference were measured. Results: According to HEI scores, only two (0.3%) of adolescents had high quality diet, 379 (63.4%) had diet quality that needed improvement and 217 (36.3%) had poor diet. Regarding Eating Attitude Test scores, 513 (85.8%) had normal attitudes regarding eating behaviors. Conclusion: Almost all of the participants need either development or major changes in their eating behaviors. Interventions aiming high quality diet among adolescents are strongly recommended.
Keywords: Adolescents; Dietary patterns; Eating disorders; Healthy eating index; Nutritional status